2018
DOI: 10.1002/etc.4242
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diltiazem on Fathead Minnows Across Dissolved Oxygen Gradients

Abstract: Water resources in many arid to semi-arid regions are stressed by population growth and drought. Growing populations and climatic changes are influencing contaminant and water chemistry dynamics in urban inland waters, where flows can be dominated by, or even dependent on, wastewater effluent discharge. In these watersheds, interacting stressors such as dissolved oxygen and environmental contaminants (e.g., pharmaceuticals) have the potential to affect fish physiology and populations. Recent field observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 106 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…Behaviour is a direct reflection of neural activity. Fish can make a series of behavioural responses to external stimuli, such as light (Karakatsouli et al 2007;Higgs et al 2018;Malambugi et al 2020), water quality (Braun & Perry 2010;Longhini et al 2017;Saari et al 2018), and breeding density (Hong et al 2019) and flow (Breitburg et al 1995). For example, some fish species can reduce irritation by moving away from light sources (Hannah et al 2015;Karlsen et al 2015;Santos et al 2019).…”
Section: Behaviours Of Fishmentioning
confidence: 99%
“…Behaviour is a direct reflection of neural activity. Fish can make a series of behavioural responses to external stimuli, such as light (Karakatsouli et al 2007;Higgs et al 2018;Malambugi et al 2020), water quality (Braun & Perry 2010;Longhini et al 2017;Saari et al 2018), and breeding density (Hong et al 2019) and flow (Breitburg et al 1995). For example, some fish species can reduce irritation by moving away from light sources (Hannah et al 2015;Karlsen et al 2015;Santos et al 2019).…”
Section: Behaviours Of Fishmentioning
confidence: 99%
“…Experimental water concentrations, plasma concentrations, and whole-body tissue concentrations for diltiazem were analytically verified by isotope dilution liquid chromatography-tandem mass spectrometry. All extractions and analysis followed previously reported methods (Du et al 2014(Du et al , 2016Bean et al 2018;Haddad et al 2018;Saari et al 2018). Briefly, 500 mL of water was collected from each exposure tank.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Fish tissue homogenates were stored at −20 °C prior to extraction and analysis. Instrument parameters are provided in detail elsewhere (Saari et al 2018). Method detection limits were 0.31 ng/L for water, 0.06 µg/kg for tissue, and 0.06 ng/mL for plasma.…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Field studies have shown that fish plasma diltiazem concentrations can exceed human plasma therapeutic values (Saari et al, 2017; Scott et al, 2016), indicating the potential for biological effects. In fish, diltiazem effects include impaired behavior (Saari et al, 2018), altered antioxidant status, modifications in key enzyme activities, and histological damage to tissues (Steinbach, Burkina, et al, 2016), while diltiazem also exacerbates the effects of low dissolved oxygen on swimming performance in fathead minnows (Saari et al, 2020). Critically, measured plasma diltiazem concentrations in field‐collected fish can exceed those predicted by modelling by more than an order of magnitude (Scott et al, 2016).…”
Section: Introductionmentioning
confidence: 99%